1997
DOI: 10.1007/bf01709474
|View full text |Cite
|
Sign up to set email alerts
|

A case of primary cutaneous cryptococcosis

Abstract: The case of a 77-year-old man in whom a large digital ulcer with undermined edges was due to cutaneous infection by Cryptococcus neoformans variety neoformans serotype D, probably following direct inoculation, is reported. Long-term steroid treatment for chronic obstructive pulmonary disease may have been a risk factor. A 12-day course of intravenous amphotericin B at a cumulative dose of 750 mg, followed by oral fluconazole at a daily dose of 600 mg for six weeks, resulted in healing of the skin lesion. Manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…While a study on clinical isolates from all over the world [13]showed mostly Cryptococcus of the serotype A (70% serotype A, 16% serotype D or AD, 11% serotype B and 2% serotype C) in patients with systemic cryptococcosis, a review of the literature indicates that primary cutaneous cryptococcosis is mostly associated with serotype D [10, 14, 15]as seen in our patient. The determination of the serotype may therefore be helpful in differentiating systemic from cutaneous cryptococcosis which is important for treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While a study on clinical isolates from all over the world [13]showed mostly Cryptococcus of the serotype A (70% serotype A, 16% serotype D or AD, 11% serotype B and 2% serotype C) in patients with systemic cryptococcosis, a review of the literature indicates that primary cutaneous cryptococcosis is mostly associated with serotype D [10, 14, 15]as seen in our patient. The determination of the serotype may therefore be helpful in differentiating systemic from cutaneous cryptococcosis which is important for treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus neoformans is a ubiquitous yeast that is commonly found in soil, especially in association with pigeon droppings (250). Infection usually occurs via the inhalation of soil aerosols, although rare cases of disease due to percutaneous inoculation have been reported (379). The clinical manifestations of cryptococcal disease depend on the host.…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 99%
“…Involvement of the skin can result in a great variety of lesions, most commonly affecting the face and neck, from papules, nodules, acneiform lesions, granulomas, herpetiform vesicles, abscesses, and ulcers, resembling other cutaneous disease, such as moUuscum contagiosum, vasculitis, Kaposi's sarcoma, varicella, basal cell carcinoma, cellulitis, cutaneous ulcération, atypical mycobacteriosis and whitlow (5)(6)(7)(8). The two forms of histological manifestation are gelatinous and granulomatous reactions.…”
Section: Discussionmentioning
confidence: 98%
“…The two forms of histological manifestation are gelatinous and granulomatous reactions. While the granulomatous type results in pronounced tissue reaction, with histiocytes, giant cells, lymphocytes, and fibroblasts, with a low number of yeasts, that vary in size from 2 to 20 [xm, in the gelatinous type, masses of organisms occur, with the accumulation of cryptococcal capsular polysaccharide causing mucoid degeneration ofthe invaded tissue, with only minimal signs of inflammation (6).…”
Section: Discussionmentioning
confidence: 99%